2021
DOI: 10.1186/s12889-021-11701-z
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis of determinants of polygyny among married men in Ethiopia

Abstract: Background Polygyny occurs when a man has more than one wife at the same time. It often contributes to poor health among family members, particularly young children. It encourages the spread of sexually transmitted infections (STIs) including HIV/AIDS. The determinants of polygyny have not yet been adequately explored in Ethiopia. This study adds to the body of knowledge concerning the prevalence and distribution of polygyny in the country. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Beliefs of privacy have also compelled such women to have their deliveries conducted at home usually by relatives or traditional birth attendants (Faye et al, 2011;Alatinga et al, 2021). Another reason could be that polygynous marriages are associated with lower levels of education among the spouses (Bove and Valeggia, 2008;Mabaso et al, 2018;Damtie et al, 2021), and lower educational attainment is associated with less utilisation of skilled birth providers services (Amponsah et al, 2021). In addition, polygynous marriages are more prevalent in rural areas in Ghana, and the use of assisted skilled birth services is limited in such areas (Lawson and Gibson, 2018); Adam et al, 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Beliefs of privacy have also compelled such women to have their deliveries conducted at home usually by relatives or traditional birth attendants (Faye et al, 2011;Alatinga et al, 2021). Another reason could be that polygynous marriages are associated with lower levels of education among the spouses (Bove and Valeggia, 2008;Mabaso et al, 2018;Damtie et al, 2021), and lower educational attainment is associated with less utilisation of skilled birth providers services (Amponsah et al, 2021). In addition, polygynous marriages are more prevalent in rural areas in Ghana, and the use of assisted skilled birth services is limited in such areas (Lawson and Gibson, 2018); Adam et al, 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Age may influence the prevalence of polygyny [ 8 ]. Many studies have identified polygyny as one of the factors that influence early marriage [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polygyny has become more common due to religion, particularly Mormonism and Islam. Age, place of residence, and household wealth all influence the prevalence of polygyny [ 8 ]. Other major factors influencing polygyny acceptance include culture and tradition.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the outcome (IPV) was spatially analyzed to unveil the heterogeneity of IPV across provinces in each country. Studies found that the likelihood of IPV was higher among women in polygynous unions [ 47 , 60 , 65 67 ].…”
Section: Methodsmentioning
confidence: 99%